Low-Coherence Interferometry for Measurement of Properties of Optical Components - Daniel Kacik; Norbert Tarjanyi; Ivan Turek (Communications - Scientific letters of the University of Zilina, 2010)
We present a modification of the interferometric method for the measurement of refractive index or thickness of optical devices using an easily aligned, almost all-fiber Michelson interferometer. Applicability of the method is demonstrated by the chromatic dispersion measurement of photonic crystal fiber sample. The birefringence of the optical device based on LiNbO3 obtained from the measurement of refractive indices is demonstrated and its value is determined for two different crystal samples. It is also shown that when the thickness of, for example, photopolymer material is known the refractive index of the device can be determined. The described method can be a practical tool for laboratories with the need of inexpensive and easily built setup for measurement of refractive index or thickness of optical devices even in a broad spectral range.